General Data Protection Regulation (GDPR): Legal, Ethic and Other Issues, Especially in Covid-19 Time - Guerra, Ana Isabel; Machado, Maria João; Fernandes, Maria Malta; Azevedo, Patrícia Anjos; Tomás, Sérgio Tenreiro; Machado, Susana Sousa (Law, State and Telecommunications Review, 2021)
[Purpose] This paper intends to present an academic analysis about the legal, ethic and other issues raised by the General Data Protection Regulation, especially in Covid-19 time. In this context, we present the main legal aspects of networked privacy, online privacy literacy, transparency, data integrity and others. Besides, we present the employee´s rights in the context of the Covid-19 pandemic, such as the right to erase data, temperature monitoring, the employee´s consent, the legitimation of the processing of personal data and body temperature control. We also give a word about data protection and teleworking. Our purpose is to contribute for the evolution of law, regarding the challenges and all the changes in our daily-life, provoked by the Covid-19 pandemic. [Methodology] Our objectives are fundamentally achieved with a legal and doctrinal analysis, which is our methodology. The topics presented in this paper are linked between each other and this kind of joint treatment is our goal. [Findings] Privacy is a broad concept that includes a set of personal characteristics that go beyond a user's name and location. Personal data includes the fundamental rights that privacy helps to guarantee. The GDPR is a legal basis for the processing of personal data, which is directly applicable in the European Union and does not require national transpositions. Employers are facing increasingly complex challenges in the day-to-day of their companies, given the need to stop the spread of coronavirus. To respond to the growing threat of coronavirus, many employers are considering monitoring the health of their employees to minimize the risk of infection and contagion in the workplace. Consent as a free, informed and unequivocal manifestation, required by the GDPR, collides with the existing asymmetries in the employment relationship. Despite all the difficulties in framing consent, it is unequivocal that the employment relationship requires the collection and processing of numerous employee data. It is an inevitability. Teleworking, provided from the employee's home, was one of the first measures adopted in the context of the pandemic caused by the Covid-19 disease. This type of work provision raises a number of questions regarding the protection of employees' personal data, namely in terms of control by the employer.